2020
DOI: 10.2166/wcc.2020.244
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-temporal trends analysis of flood events in the Republic of Armenia in the context of climate change

Abstract: The primary goal of the study is to analyze the spatial-temporal trends and distribution of flood events in the context of climate change in Armenia. For that purpose, some meteorological parameters, physical-geographical factors and the flood events data were studied for the 1994–2019 period. The linear trends demonstrate an increasing tendency of air temperature and precipitation. Those trends expressed increased flood occurrences, especially for the 2000s, whereas Mann–Kendall (MK) trend test reveals no sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In terms of climate change, being a mountainous area with arid climatic conditions, Syunik province is vulnerable (Melkonyan and Gevorgyan, 2020). During the last two decades , the average air temperature from March to August in Syunik province increased by about 1.5 C (Galstyan et al, 2020). The spatial distribution of changes in precipitation is irregular in the RA.…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of climate change, being a mountainous area with arid climatic conditions, Syunik province is vulnerable (Melkonyan and Gevorgyan, 2020). During the last two decades , the average air temperature from March to August in Syunik province increased by about 1.5 C (Galstyan et al, 2020). The spatial distribution of changes in precipitation is irregular in the RA.…”
Section: Study Areamentioning
confidence: 99%
“…The spatial distribution of changes in precipitation is irregular in the RA. Over the last 80 years, the climate in Syunik province has turned arider (Gevorgyan, 2012;Galstyan et al, 2015;Galstyan et al, 2020;Melkonyan and Gevorgyan, 2020).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…It has become increasingly clear that one of the major hydrological impacts associated with current climate warming is the increase in magnitude (intensity) and frequency of floods. This hydrological change has been increasingly documented in many regions of the world (e.g., Berghuisjs et al, 2017;Collins, 2019;Dube et al, 2022;Galstyan et al, 2020;Hannaford & Marsh, 2008;Hodgkins et al, 2017Hodgkins et al, , 2019Kemter et al, 2020;Kimuli et al, 2021;Llasat et al, 2016;Mallakpour & Villarini, 2015;Mangini et al, 2018;Mao et al, 2019;Najibi & Devineni, 2018;Nka et al, 2015;Paprotny et al, 2018;Tabari, 2020;Tellman et al, 2021;Tramblay et al, 2019Tramblay et al, , 2020Wasko et al, 2020). However, in their extensive study on the spatiotemporal variability of floods across the European continent, Blöschl et al (2019) demonstrated that this increase in flood frequency and intensity has not occurred consistently over the past five decades in the continent as a whole.…”
Section: Introductionmentioning
confidence: 99%